Jurnal Pekerjaan Sosial: PENGEMBANGAN DESAIN KONSELING INSTRUKSI DARI DIRI (INDARI) DALAM MENINGKATKAN MOTIVASI PENERIMA MANFAAT MENGIKUTI PELATIHAN KETERAMPILAN TATA BOGA DI PANTI PELAYANAN SOSIAL PGOT MARDI UTOMO SEMARANG - Laela Aini; Dwi Heru Sukoco; Rini Hartini Rinda Andayani (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2023)
INDARI counseling is a social work innovation technology that combines counseling with habituation and strengthening positive verbalization in oneself in the form of positive affirmations and self-talk. This study aims to determine the effect of INDARI Counseling which aims to increase the motivation of beneficiaries, especially in participating in culinary training at Panti Mardi Utomo Semarang. In line with the purpose of implementing services for orphanages that have poverty settings so that beneficiaries can be independent after the service period at the orphanage ends. The behavioral indicators of lack of motivation measured include lack of discipline when attending, lack of responsibility in doing assignments, lack of concentration in attending training, and not having plans for the future. The research method used is single subject design A-B-A. The subjects in this study were beneficiaries of the PGOT Mardi Utomo Social Service Institution in Semarang who participated in culinary skills training. The data sources used are primary and secondary data sources. The validity test of the measuring instrument used in this study is the face validity test, while the reliability test of the measuring instrument uses the percent agreement. The results showed from the trend of the graph direction, data analysis under conditions and between conditions, it can be concluded that the implementation of INDARI counseling can be one of the techniques that can be used to increase client motivation in participating in skills training.